2022
DOI: 10.3390/nu14030655
|View full text |Cite
|
Sign up to set email alerts
|

Terminology Matters: Advancing Science to Define an Optimal Pulse Intake

Abstract: Confusion around the terms “legumes” and “pulses” has been a long-standing problem among consumers, health professionals, and researchers in the United States. The Food and Agricultural Organization defines pulses as legumes that are harvested solely as dry grain and include beans, peas, chickpeas, and lentils. For the first time ever, the 2020–2025 Dietary Guidelines for Americans recognized and used the terminology “pulses.” Correct terminology usage is important to build a solid research foundation that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Legumes can be divided into two main categories: (1) oilseed legumes which provide a high amount of fat, including peanuts and soybeans, and (2) non-oilseed legumes (undried legumes and dried legumes). The dried legumes are termed “pulses”, which include beans, peas, and lentils [ 68 , 69 ]. Pulses are known for their nutrient density and health benefits, and beans are the major pulses consumed worldwide [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legumes can be divided into two main categories: (1) oilseed legumes which provide a high amount of fat, including peanuts and soybeans, and (2) non-oilseed legumes (undried legumes and dried legumes). The dried legumes are termed “pulses”, which include beans, peas, and lentils [ 68 , 69 ]. Pulses are known for their nutrient density and health benefits, and beans are the major pulses consumed worldwide [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dried legumes are termed “pulses”, which include beans, peas, and lentils [ 68 , 69 ]. Pulses are known for their nutrient density and health benefits, and beans are the major pulses consumed worldwide [ 68 , 69 ]. Therefore, we focused on ten original lineage beans in Thailand, eight of which were dried beans from the Phaseolus and Vigna genera as the representatives of non-oilseed legumes, including three types of the underutilized lima beans, three types of commonly consumed red beans, and commonly consumed mung bean and black gram.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, different PLS regression models for such crops should be trained to overcome matrix differences compared to chickpeas. Apart from chickpeas, the fat composition in other pulses is ∼1–2% since pulses are not oil-seed crops. Accordingly, this FT-MIR technique has limitations over such samples since the limit of detection (LOD) of the instrument is about 1%, and the associated FT-MIR signals are not distinct (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Participants on a diet with positive immunomodulatory effects were also found to have the highest intake of nuts and pulses, which contain high amounts of fiber, resistant starch, arginine, vitamins, minerals, and other bioactive components [ 53 ]. Numerous studies confirmed the beneficial effects of walnut, pistachio, or almond consumption on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%